VD_FINDINFO HC / 2020 / 155 vom 11. Februar 2020 - VD Tribunal cantonal (2020)
ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL, COMMANDEMENT DE PAYER, OPPOSITIONPROCÉDURE, RESPONSABILITÉ CONTRACTUELLE, RESPONSABILITÉ DÉLICTUELLE | 41 CO, 97 CO